The relationship between license type and alcohol-related problems attributed to licensed premises in Perth,Western Australia - Stockwell, Tim; Somerford, P.; Lang, E. (1992)
Drink-driving offenses, alcohol-related traffic accidents and number of assault charges were used as indicators of the degree of alcohol-related problems associated with individual licensed premises in the Perth Traffic Police region of Western Australia.These indicators were used to rank five main categories of licenses premises according to the levels of harm experienced by their customers while controlling for the amounts of alcohol sold in each category.Nightclubs,taverns and hotels emerged as "high risk" in comparison with clubs and restaurants.The role of such factors as different customer characteristics, opening hours, types of entertainment, restrictions on clientele and provision of meals are discussed as possible explanations underlying this finding. (J. Stud. Alcohol 53:495-498, 1992)